Glovebox-CT to Enable 3D Imaging of Reactive or Hazardous Samples - Nick Brierley; Darius Zanke; Luke Peche; Peter Habenschaden (e-Journal of Nondestructive Testing)
In the development of new technologies, sophisticated materials often require a highly pure inert atmospheres, for example with less than 1 ppm of oxygen and moisture. Additionally, special protection for operators is frequently necessary due to the health and environmental risks posed by these materials. To address this need, diondo and MBRAUN have been collaborating to develop an X-ray CT scanner system that allows reactive or hazardous materials to be scanned in a highly sealed inert atmosphere. The innovative setup merges a diondo CT system with an MBRAUN glovebox. With a leakage rate of Class 1 according to ISO 10684-2, the glovebox functions as an ultra-tight containment, ensuring the integrity and safety needed for handling challenging materials, whilst the radiation enclosure ensures operators and bystanders are protected from X-rays during scanning. Combining the two forms of containment with the X-ray imaging chain is non-trivial, especially considering sample manipulation, ergonomics and maintenance. This contribution will describe the solutions adopted to meet these challenges.